Construction Cost Reduction in Design of Prestressed Concrete Structural System - Surbakti, Michelia Esteruli Instia; Hariandja, Binsar; Bali, Ika (PRESUNIVE CIVIL ENGINEERING JOURNAL, 2024)
Concrete material has moderately strong compressive strength, but relatively weak tensile strength. To overcome this problem, three kinds of systems can be applied, namely reinforced concrete system, composite concrete system, and prestressed concrete system. In a prestressed concrete system, a compressive force is applied to annihilate the tension region in the concrete section. Compared to reinforced concrete, prestressed concrete requires a smaller section of concrete, since the whole cross section is in compression and active. However, prestressing concrete needs the use of high strength steel wire which is extremely costly. The use of prestressing concrete may be carried out using minimization on the use of such expensive high strength steel. In this research, two methods of minimization of the use of high strength steel, which are the shifting of the support of the beam to get the smaller field moment. The other method is to reshape the concrete section to have a higher moment of inertia. It is found out that the two methods perform well in the minimization process of construction cost of the prestressing concrete beam.